2017
DOI: 10.1186/s12910-017-0194-9
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on acceptable levels of risk for pregnant women in clinical research

Abstract: BackgroundThere is ambiguity with regard to what counts as an acceptable level of risk in clinical research in pregnant women and there is no input from stakeholders relative to such research risks. The aim of our paper was to explore what stakeholders who are actively involved in the conduct of clinical research in pregnant women deem an acceptable level of risk for pregnant women in clinical research. Accordingly, we used the APOSTEL VI study, a low-risk obstetrical randomised controlled trial, as a case-stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…15,18,21,23 The majority of women perceived no to very little risk of participating in the trial, and this is often a major consideration in women's decision to be involved in a study. 18,21,23,32 In particular, the knowledge that corticosteroids were already being used in pregnancy was comforting to women, which is consistent with evidence that shows drugs already used in pregnancy are more likely to be acceptable to participants in clinical trials. 23 Women felt well informed before consenting, however, some identified there was too much written information provided, while others wanted more information regarding the risk of corticosteroid administration in pregnancy.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…15,18,21,23 The majority of women perceived no to very little risk of participating in the trial, and this is often a major consideration in women's decision to be involved in a study. 18,21,23,32 In particular, the knowledge that corticosteroids were already being used in pregnancy was comforting to women, which is consistent with evidence that shows drugs already used in pregnancy are more likely to be acceptable to participants in clinical trials. 23 Women felt well informed before consenting, however, some identified there was too much written information provided, while others wanted more information regarding the risk of corticosteroid administration in pregnancy.…”
Section: Discussionsupporting
confidence: 72%
“…Pregnant populations were at significant risk of harm due to COVID‐19 infection, and rapid evidence to support the safety of vaccination in this group was needed, however, women were hesitant to participate in clinical trials 31 . Clinicians report challenges in encouraging women to participate in clinical trials and have highlighted several barriers to ensuring a clinical trial is conducted as intended 22,25,26,32 . Understanding clinician perspectives about their involvement in the administration of clinical research is important in the development and implementation of study protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Based on safety concerns a similar restrictive, protective gatekeeping role is often taken in the involvement of pregnant women in medical research and pharmaceutical interventions during pregnancy, as is also demonstrated by some of our findings [22, 4951] This position reveals a precautionary principle attitude, i.e. to avoid an action altogether if the action carries the potential to cause significant harm, even if this is highly unlikely [52].…”
Section: Discussionmentioning
confidence: 55%
“…One of the reasons concerns the individual risk perception of researchers, research ethics committees, sponsors and pregnant women themselves which plays an important role in the inclusion of pregnant women. Even if the research intervention poses low risks and may potentially benefit the pregnant women, when researchers perceive a trial to pose more than low risks to their patients they may be reluctant to recruit eligible participants (gatekeeping) and pregnant women may be reluctant to participate [38]. Second, for many drugs used by pregnant women the purpose will often not be to determine differences in efficacy between pregnant women and non-pregnant women but rather to determine aspects such as effectiveness and safety, including birth defects and teratogenicity.…”
Section: Resultsmentioning
confidence: 99%